Attacking process characterization of elite water polo female teams - S. Canossa; J. Garganta; M. Lloret; F. Argudo; R. Fernandes (Desafio Singular, 2009)
The purpose of the present study was to analyze the attacking tasks and tactical organization of elite Women's Water Polo. The sample consisted of 442 attack sequences of 8 games played by the top teams in a European Championship. Seventeen variables were analyzed according to the position and player's participation, tactical organization and playing styles, as well as the efficacy of actions performed. The results from this study indicate that positional attack was the predominant performance factor in the attacking process. To this occurrence, the mixed floating defense was identified as the most frequent opposition. The counter-attack proved to be the most efficient strategy. The attacking process frequently started by ball recovering, in anticipation, and by the defense of the goal-keeper in the 2m zone. In central path, a first long-range pass to the right wing predominated. Teams preferred spontaneous shot on goal supported by assisted displacements, and extra player man offence situations. In general, the attacking sequences, do not take longer than 35s to be developed.) Teams efficiency emerged related to the tactical means adopted, namely the spontaneous shot at goal on the front line and numerical superiority of players in attacking game situations.